Institutional Policies and Practices for Admitting, Assessing, and Tracking International Students - Andrade, Maureen Snow (Journal of International Students, 2017)
The United States has the largest market share of international students at 22%, followed by the United Kingdom at 11% (Project Atlas, 2015). The U.S. share has decreased from 28% in 2001 although total numbers ofinternational students are increasing (Project Atlas, 2015). Decreased market share may be due to targeted national strategies in other countries to attract international students. These include immigration policies that not only expedite obtaining a student visa, but provide opportunities to work while studying and permanent jobs and residency after graduation (e.g., Canada, the Netherlands, Germany, Sweden) (Lane, 2015). Nations are also actively recruiting, providing databases with comprehensive information about studying in the country, (e.g., the Netherlands), and offering financial incentives (e.g., Germany)(Lane, 2015). In some cases, countries that once sent students to study abroad (United Arab Emirates, Singapore, Malaysia) are now actively recruiting to host students from their regions (Lane, 2015).